Lairds of Suburbia: Scottish Migrant Settlement and Housing in Australian Cities, 1880–1930. Issue 1 (May 2016) - Wilkie, Ben
Abstract : Drawing on decennial population statistics from 1881 to 1933, this article evaluates the settlement patterns of Scottish migrants in Australian cities. It considers the urban nature of Scottish settlement, and argues that settlement patterns were associated with employment opportunities for working-class Scots, along with various housing, lifestyle, and religious preferences, often grounded in pre-migration experiences of city living. Furthermore, this article demonstrates that Scottish migrants in Australia at the turn of the twentieth century largely belonged to an urban industrial working class, and provides a useful correction to the traditional images of Scots in Australia as mostly rural, well-off, and conservative migrants.